Effects of Huperzine Used As Pre-Treatment Against Soman-Induced Seizures - Tonduli, L.S; Testylier, G; Masqueliez, C; Lallement, G; Monmaur, P (Neurotoxicology (Park Forest South), 2001)
Huperzine A (HUP), an alkaloid isolated from the Chinese club moss, Huperzia serrata, is a reversible inhibitor of cholinesterases which crosses the blood-brain barrier and shows high specificity for acetylcholinesterase (AChE) and a prolonged biological half-life. We tested, in vivo, its efficiency in protecting cortical AChE from soman inhibition and preventing subsequent seizures. The release of acetylcholine (ACh) was also followed in the cortex of freely moving rats using microdialysis techniques. We previously found that soman-induced seizures occurred in rodents only when the cortical AChE inhibition was over 65% and when the increase of ACh level was over 200 times the baseline level. This was verified in the present study in control animals intoxicated by 1 LD 50 of soman (90 μg/kg). Using the same dose of soman in rats pre-treated with 500 μg/kg of HUP, we observed that 93% of the animals survived and none of them had seizures. This dose of HUP reduced AChE inhibition to 54% and increase of ACh level to 230 times baseline value. HUP thus appears as a promising compound to protect subjects against organophosphorus intoxication.